Diabetes exacerbates SARS-CoV-2 replication through ineffective pulmonary interferon responses, delayed cell-mediated immunity, and disruption of leptin signaling - Thieulent, Côme J.; Balasuriya, Udeni B. R.; Tseng, Anna; Crossland, Nicholas A.; Stephens, Jacqueline M.; Dittmar, Wellesley; Staszkiewicz, Jaroslaw; Richt, Juergen A.; Carossino, Mariano (Frontiers in Cellular and Infection Microbiology, 2025)
Comorbidities, including obesity and type 2 diabetes mellitus (T2DM), are associated with increased disease severity and mortality following SARS-CoV-2 infection. Here, we investigated virus-host interactions under the effects of these comorbidities in diet-induced obesity (DIO) and leptin receptor-deficient (T2DM) mice following infection with SARS-CoV-2. DIO mice, as well as their lean counterparts, showed limited susceptibility to SARS-CoV-2 infection. In contrast, T2DM mice showed exacerbated pulmonary SARS-CoV-2 replication and delayed viral clearance associated with down-regulation of innate and adaptative immune gene signatures, ineffective type I interferon response, and delayed SARS-CoV-2-specific cell-mediated immune responses. While T2DM mice showed higher and prolonged SARS-CoV-2-specific immunoglobulin isotype responses compared to their lean counterparts, neutralizing antibody levels were equivalent. By silencing the leptin receptor in vitro using a human alveolar epithelial cell line, we observed an increase in SARS-CoV-2 replication and type I interferons. Altogether, our data provides for the first time evidence that disruption of leptin receptor signaling leading to obesity and T2DM induces altered type I interferon and cell-mediated responses against SARS-CoV-2, mediating increased viral replication and delayed clearance. These data shed light on the alteration of the innate immune pathway in the lung using in-depth transcriptomic analysis and on adaptive immune responses to SARS-CoV-2 under T2DM conditions. Finally, this study provides further insight into this risk factor aggravating SARS-CoV-2 infection and understanding the underlying cellular mechanisms that could help identify potential intervention points for this at-risk population.